Incidence and determinants of neonatal mortality in the first three days of delivery in northwestern Ethiopia: a prospective cohort study - Mulugeta Dile Worke; Afework Tadele Mekonnen; Simachew Kassa Limenh (BMC, 2021)
Abstract Background Addressing sustainable development goals to reduce neonatal mortality remains a global challenge, and it is a concern in Ethiopia. As a result, the goal of this study was to assess the incidence and determinants of neonatal mortality in the first 3 days among babies delivered in the referral hospitals of the Amhara National Regional State. Methods A hospital-based prospective cohort study was conducted among 810 neonates in the first 3 days of delivery between March 1 and August 30, 2018. The neonates were followed up from the time of admission to 72 h. Interviewer-administered questionnaires and medical record reviews were conducted for data collection. Data were entered into Epi-data manager version 4.4 and analysed using STATA™ version 16.0. The neonate's survival time was calculated using the Cox-Proportional hazards model. Results The overall incidence of neonatal mortality in this study was 151/1000 births. Neonatal mortality was significantly higher among neonates whose mothers came between 17 and 28 weeks of gestation for the first visit; among those whose mothers labour was not monitored with a partograph, mothers experienced postpartum haemorrhage and developed a fistula first 24 h, and experienced obstructed labour. However, 39% were less risky among neonates whose mothers were directly admitted and whose mothers had visited health facilities in less than 1-h, both. Conclusions This study revealed that approximately 1 in 7 neonates died within the first 3 days of life. The determinants were the timing of the first antenatal visit, quality of labour monitoring, maternal complications, and delay in seeking care. Thus, scaling up evidence-based interventions and harmonising efforts to improve antenatal care quality, promote institutional deliveries, provide optimal essential and emergency obstetric care, and ensure immediate postnatal care may improve neonatal survival.